2019
DOI: 10.3389/fpsyt.2019.00535
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Psychopathological Comorbidities in Children and Adolescents With Autism Spectrum Disorder Using the Child Behavior Checklist

Abstract: Autism spectrum disorder (ASD) is characterized by psychiatric and behavioral comorbidities. The Child Behavior Checklist (CBCL) provides valid and well-established measures of emotional, behavioral, and social problems in children and adolescents. The aim of the present study was to verify whether emotional, behavioral, and social problems were modulated by ASD symptom severity, cognitive development, gender, and age by analyzing the CBCL in a large group of children and adolescents with ASD. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 48 publications
4
38
0
2
Order By: Relevance
“…This finding means that internalizing problems may overlap across the three groups. Our findings also confirm the high sensitivity of the CBCL for the internalizing symptoms previously described around 30%, in line with Guerrera et al (2019). This result confirms that CBCL is a specific instrument to measure internalizing symptoms in ASD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding means that internalizing problems may overlap across the three groups. Our findings also confirm the high sensitivity of the CBCL for the internalizing symptoms previously described around 30%, in line with Guerrera et al (2019). This result confirms that CBCL is a specific instrument to measure internalizing symptoms in ASD.…”
Section: Discussionsupporting
confidence: 91%
“…The Child Behavior Checklist (CBCL; Achenbach and Rescorla, 2001) is a well-established and widely used parentcompleted measure of emotional and behavioral symptoms in children and adolescents aged 1.5-18 years (Sokolova et al, 2017;Guerrera et al, 2019). The CBCL results in a guided description of the child by the parents, whose fidelity in reporting symptoms is also widely recognized for psychopathological conditions and behavioral problems associated with ADHD and ASD, as recently shown by Guerrera et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them were compared with other disorders on one or two symptoms, such as depression [19] and obsessive-compulsive disorder [20], or evaluated with associated symptoms of autism [21]. What is consistent with our research results is that, in Anderson's studies about network analysis of autism, "social" and "communication" domains of Autism Diagnostic Observation Schedule (ADOS) ranked top two central items [21]; and the "anxiety" node in both ADOS and Revised Child Anxiety and Depression Scale (RCADS) items were highly peripheral [12,21], although previous study found a lack of correlation between items scores of CBCL and ADOS [22,23]. Here, "communication" was the most central node in the network, and "anxious/depressed problems" node in the CBCL items had relatively more peripheral centrality estimates.…”
Section: Central Symptoms In Asdsupporting
confidence: 88%
“…The calibrated severity score (CSS) index from 4 to 10 was used to quantify autism symptoms independently from patients’ characteristics, such as age and language level (Gotham, Pickles, & Lord, 2009). The Child Behavior Checklist (CBCL) was used to assess a range of emotional and behavioral difficulties (Guerrera et al, 2019). Cutoff scores ≥60 for internalizing, externalizing and total T ‐scores were considered.…”
Section: Methodsmentioning
confidence: 99%